In vivo skin permeation study of medium-chain triacylglycerols (MCTSs) / Muhammad Syafiq Aiman Mohd Kamil - Mohd Kamil, Muhammad Syafiq Aiman (2013)
This study was carried out to investigate the in vivo skin permeation of u-tocopherol in medium chain triacylglycerols (MCTs) vehicles namely virgin coconut oil (VCO) and structured virgin coconut oil (SVCO) creams. MCTs act as permeation enhancers in pharmaceutical and cosmeceutical formulations. VCO contains mainly of 12 carbon chain lengths and lauric acid whereas SVCO which was produced by acidolysis of caprylic acid and VCO contains 60% of caprylic acid with 8 carbon chain lengths. The skin tape- stripping technique was applied to evaluate the level of n-tocopherol retained in the stratum corneum (SC). The amount of u-tocopherol was quantified using high performance liquid chromatography (HPLC). The results showed that both permeation enhancers increased the permeation of u-tocopherol into the stratum corneum, viable skin and the skin surface. The amount of a tocopherol recovered from the skin surface by VCO was 55 ± 12% and SVCO was 60 ± 11 %. The amount of u-tocopherol recovery from viable skin by VCO was 6 ± 13% and SVCO was 7 ± 14% while the amount of n-tocopherol recovery from stratum corneum by VCO was 11 ± 12% and SVCO was 12 ± 13% respectively. In conclusion MCTs creams promote the permeation of u-tocopherol into the stratum corneum, viable skin and skin surface by modulating the barrier function of the skin.